A prospective observational study on thyroid malignancy - V., Bharath S.; Lakshminarayana, Badareesh; Mehta, Rishabh (International Surgery Journal, 2021)
Background: Thyroid cancers are a complex group of tumours with wide variety of histological presentation and biological behaviour, and prognosis range. In their early stages, they behave like other benign conditions of the thyroid. The success of treatment lies upon early diagnosis and proper management. The aim of the present study is to evaluate the modes of presentation, the incidence of various pathological types, and assess their clinical, behaviour and surgical management. Methods: The present study is observational, time-bound, consists of patients prospectively and consecutively diagnosed and histologically confirmed thyroid malignancy. Results: This study showed females 80.66% are commonly affected than males 19.44%. The most frequent malignancy is papillary 86.11%, followed by follicular carcinoma 11.11%, medullary carcinoma 2.78%. Cervical lymph nodes are involved in four 13.88% of patients. In patients undergone iodine ablation, 5.56% of them had a recurrence. Mortality at two years was 2.7%. In this study, Thyroid cancer is commonly seen between twenty-one to thirty years. Conclusions: The incidence of thyroid malignancies is more common among women (80.66%) than men. Papillary carcinoma (86.11%) is the common differentiated thyroid cancer. The prevalence of distant metastasis is 2.78% to the vertebral body. In our study, 41.66% of patients belongs to less than 30 years of age; this may be due to the trend of overdiagnosis due to the introduction of ultrasonography guided Fine needle aspiration study.